Conférence « Liberating the Spirit of Women as an American Value » de Carol Moseley Braun, ancienne Sénatrice américaine et Ambassadrice de Nouvelle Zélande. - Marine Dabon (Transatlantica)
This review is a summary of former American Senator and Ambassador Carol Moseley Braun’s speech during a conference entitled « Liberating the Spirit of Women as an American Value », organized by Hélène Quanquin and Christine Zumello and held on November 16th in université Sorbonne Nouvelle.